Landscape spatial pattern indices and soundscape perception in a multi-functional urban area, Germany - Liu, Jiang; Kang, Jian; Behm, Holger; Luo, Tao (Journal of Environmental Engineering and Landscape Management, 2014)
Soundscape research could provide more information about urban acoustic environment, which should be integrated into urban management. The aim of this study is to test how landscape spatial pattern could affect soundscape perception. Soundscape data on specifically defined spatial and temporal scales were observed and evaluated in a multi-functional urban area in Rostock, Germany. The results show that urban soundscapes were characterised by artificial sounds (human, mechanical and traffic sounds) overwhelming the natural ones (biological and geophysical sounds). Major sound categories were normally mutual exclusive and dynamic on temporal scale, and have different spatial distribution on spatial scale. However, biological and traffic sounds seem to be co-existing on both temporal and spatial scales. Significant relationships were found existing between perception of major sound categories and a number of landscape spatial pattern indices, among which vegetation density (NDVI), landscape shape index (LSI) and largest patch index (LPI) showed the most effective indicating ability. The research indicated that soundscape concepts could be applied into landscape and urban planning process through the quantitative landscape indices to achieve a better urban acoustic environment. First published online: 28 May 2014